Cōmavāra virata makimai : Tiruñāṉacampanta Cuvāmikaḷ aruḷiya tiruvālavāy tirunīṟṟup patikattuṭaṉ - Kaṇapatippiḷḷai, Mu (s.n.], 1981)
On the significance of a fast observed by devout shaivitis on mondays; includes a verse work by Campantar, 7th cent.